Social support relationships for sexual minority women in Mumbai, India: a photo elicitation interview study. Issue 2 (1st February 2018) - Bowling, Jessamyn; Dodge, Brian; Banik, Swagata; Bartelt, Elizabeth; Mengle, Shruta; Guerra-Reyes, Lucia; Hensel, Devon; Herbenick, Debby; Anand, Vivek
Abstract: Little research exists on women who do not identify as heterosexual in India. Social support for sexual minority women may protect against the effects of discrimination. An examination of significant social relationships may point to both strengths and weaknesses in this support. We aimed to understand relationship prioritisation and communication patterns associated with the social support of sexual minority women in Mumbai. In partnership with the Humsafar Trust, India's oldest and largest sexual and gender minority-advocacy organisation, we conducted photo-elicitation interviews with 18 sexual minority women, using participants' photographs to prompt dialogue about their social support. Intimate partners were a source of dependable support and many of those without relationships were seeking them. Participants' extended networks included friends and family as well as less formal relationships of social support. Participants mediated their communication with particular social network members, which involved filtering information sexual identity, romantic interests, and personal aspirations, among others. The diverse relationships that sexual minority women have in their social support networks may be used to guide programmes to improve health outcomes.